The Influence of PT Bobotoh Indonesia Gemilang's Internal Communication on Employee Attitudes in Supporting Persib Bandung - Ajeng Daningtyas Widiarizki (MEDIALOG: Jurnal Ilmu Komunikasi, 2021)
PT Bobotoh Indonesia Gemilang is one of the companies that has a clear collective identity, namely Bobotoh. The key to the formation of organizational identity is the effectiveness of internal communication within the organization. In the KBBI, bobotoh means football supporter. However, because in Sundaland itself, Persib is one of the big teams, so the meaning of bobotoh itself is more focused on Persib supporters. Engaged in trade and media, PT. BIG has a media called Bobotoh.ID. Then in the trade sector, to be precise in the distribution of goods, a subsidiary of PT BIG named Bobotoh Kopi Gadjah. The two subsidiaries use the identity of bobotoh. The purpose of this research is to find out how much influence the internal communication of PT BIG has on the attitude of employees in supporting Persib Bandung. The method used in this study is an explanatory survey method. With a population of employees of PT BIG amounting to 21 people and the same number of samples because it uses the saturated sample method. The results obtained, the value of R (correlation) between variable X and variable Y is 0.601 which means that the relationship between the Internal Communication variable (X) and Attitude (Y) is quite strong. Then, the result of T count is 3.274>T Table 2.07961 and a significance value of 0.004 <0.05, so Ho is rejected and Hi is accepted. This means that the internal communication of PT. BIG has an effect on the attitude of employees in supporting Persib.